Involvement of obliquus capitis inferior muscle in dystonic head tremor - Schramm, Axel; Huber, D.; Möbius, Cornelia; Muenchau, A.; Kohl, Zacharias; Baeumer, T. (Parkinsonism & Related Disorders, 2017)
Head tremor is a common feature in cervical dystonia (CD) and often less responsive to botulinum neurotoxin (BoNT) treatment than dystonic posturing. Ultrasound allows accurate targeting of deeper neck muscles.In 35 CD patients with dystonic head tremor the depth and thickness of the splenius capitis (SPL), semispinalis capitis and obliquus capitis inferior muscles (OCI) were assessed using ultrasound. Ultrasound guided EMG recordings were performed from the SPL and OCI.Burst-like tremor activity was present in both OCI in 25 and in one in 10 patients. In 18 patients, tremor activity was present in one SPL and in 2 in both SPL. Depth and thickness of OCI, SPL and semispinalis capitis muscles were very variable.Muscular activity underlying tremulous CD is most commonly present in OCI. Due to the variability of muscle thickness, we suggest ultrasound guided BoNT injections into OCI.
EVALuna2:22566